1999
DOI: 10.1007/s002679900166
|View full text |Cite
|
Sign up to set email alerts
|

Conservation in Brazil's Chocolate Forest: The Unlikely Persistence of the Traditional Cocoa Agroecosystem

Abstract: / In southern Bahia, Brazil, the traditional cocoa agroecosystem with a dense shade canopy of native trees is now recognized as a secondary conservation route for highly endangered Atlantic Rainforest species. This "chocolate forest" of the densely shaded farms persists despite a massive 20-year Brazilian government modernization program in which shade was seen as a chief impediment to raising cocoa production. The objective of this study was to determine how this traditional agroecosystem endured. Although de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
83
0
13

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 4 publications
0
83
0
13
Order By: Relevance
“…Although inventories that use standardized sample methods are desirable, it is interesting to point out that this percentage is, nonetheless, biologically significant. The Una region is one of the last areas that still possess some of the characteristics of the formerly extensive Atlantic Rainforest (Johns 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Although inventories that use standardized sample methods are desirable, it is interesting to point out that this percentage is, nonetheless, biologically significant. The Una region is one of the last areas that still possess some of the characteristics of the formerly extensive Atlantic Rainforest (Johns 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Other habitats outside reserves are more important and these include forest fragments and`Cabrucagem' shade cocoa plantations. Some of the more traditional cocoa growing regimes have been identi®ed as useful for nature conservation (Johns, 1998), and may be well utilised by parrots such as P. cruentata (Forshaw, 1989). Table 6 Sizes of key areas known to hold populations of P. cruentata and/or A. rhodocorytha (from Wege and Long, 1995) It may be that the preservation and regeneration of forest fragments around certain stronghold reserves may yield high returns for species conservation at comparatively low cost.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Johns (1999) reported that yield almost doubled (from 900 to 1,700 kg ha -1 of cocoa beans) with the total removal of the shade trees and use of fertilizers on a series of cocoa farms monitored by researchers of CEPLAC in the cocoa producing region of Bahia during the period 1964-1974. However, the author pointed out that this intensification package was not widely adopted by farmers, who preferred a lower-risk management approach, with occasional use of fertilizers and agrochemicals and the maintenance of shade trees, recognized for their valuable role in limiting ecological risks such as drought and outbreaks of pests and diseases.…”
Section: The Push For Full Sun Intensificationmentioning
confidence: 99%